The Influence of Self-Efficacy on Job Satisfaction, Organizational Commitment, Motivation and Job Performance in Private School Teachers - Yemima Rossiandy; Rhian Indradewa (Pelopor Publikasi Akademika, 2023)
Self-belief in an individuals abilities is essential for influencing behavior, decision-making and achieving organizational goals. The purpose of this study is to investigate the role of teacher self-efficacy that can influence job satisfaction, organizational commitment, motivation and job performance in the scope of formal education. This study used data collection by survey method and online questionnaire distribution, respondents were selected by purposive sampling method. The sample of this research is teachers who teach at the kindergarten, elementary, junior high, and high school levels in the 2022-2023 school year. The data analysis technique used Structural Equation Model (SEM) with SmartPLS 3.0. Some of the findings in this study are that self-efficacy has a direct effect on job satisfaction, motivation and job performance of teachers. Self-efficacy has no direct influence on job performance through the mediating effects of motivation and organizational commitment. The managerial implication of this study for school administrators and researchers is to strengthen the perception of teacher self-efficacy through professional development, appreciation and rewards, so that it can have a broad positive impact on teacher motivation in various aspects of life.